Pemanfatan Lahan Pekarangan Sebagai Apotik Hidup Di Dusun Banjar Punggawa, Desa Hara Banjar Manis, Kecamatan Kalianda - Sepri YH, Aryan Ari; Safitri, Anggun; Harlianda, Triyandita Kusuma (Universitas Pahlawan Tuanku Tambusai, 2025)
Banjar Punggawa Hamlet is located in Hara Banjar Manis Village, Kalianda Distric, South Lampung Regency, Lampung Province. The problem faced in Banjar Punggawa Hamlet community is that they are not fully utilizing empty land optimally. The purpose of this service is to utilize empty land for living pharmacies to the community, as well as providing knowledge and skills in managing yard land becomes a living pharmacies. The service methods used are socialization, mentoring and practice. The results of the service show that empty land that is not being used properly can be converted into a living pharmacy for the community, so that the community can have medicine supplies in the surrounding environment and utilize land that is not being used properly. In addition, providing knowledge and skills to the community in managing land yard becomes a live pharmacy. Follow-up plans or policy implications need to be carried out to increase support and assistance for the program, strengthen inter community networks and involve local governments to support sustainable development in the use of homestead land. Besides that, increasing community capacity in agricultural techniques and marketing local products can be a strategic step to increase the positive impact of this empowerment program.